Left atrial strain as a pre-operative prognostic marker for patients with severe primary mitral regurgitation. (25th November 2020) - Mandoli, G.E; Pastore, M.C; Benfari, G; Maccherini, M; Lisi, G; Cameli, P; Lisi, M; Lisi, E; Tsioulpas, C; Carrucola, C; Vigna, M; Montesi, G; et al.
Abstract: Background: For patients with severe mitral regurgitation (MR), new indices are needed to optimize surgical timing before irreversible myocardial dysfunction. Purpose: We investigated the prognostic role of left atrial (LA) strain by speckle tracking echocardiography after mitral surgery for severe MR, and its association with LA fibrosis. Methods: 70 patients with primary severe MR undergoing echocardiography before mitral surgery were enrolled. Patients with other valvular disease > moderate, left bundle branch block, coronary artery disease, heart failure (HF), pacemaker implantation, heart transplantation, poor acoustic window, were excluded. The primary composite endpoint included HF and mortality; the secondary endpoint was post-operative functional capacity (NYHA and Borg CR10). LA fibrosis was assessed by atrial biopsy specimens. Results: Of 62 patients eligible, 32 had composite events (medium follow-up: 3.3±2.5 years for event-group, 7.6±1 years for non-event group). Characteristics of our study population are summarized in Table 1. With Kaplan-Meier analysis (Fig. 1), PALS provided a good risk stratification; it also was an independent and incremental predictor of outcome in four multivariate Cox adjusted models. There was a strong association between PALS and secondary endpoint (NYHA: r2=0.11, p=0.04; Borg CR10: r2=0.10, p=0.02) and an inverse correlation between PALS <21% and LA fibrosis (r2=0.80; 76.6±20.7% vs 31.9±20.8%; p<0.0001). Conclusions: Global PALS emerged as a reliable predictor of outcome and functional capacity for severe primary MR, and as a marker of LA fibrosis. Funding Acknowledgement: Type of funding source: None